Characterization Of Oil Palm Empty Fruit Bunch and Coconut Shell for The Production of Fuel Briquettes - Manga, Gila Layindeh; Abioyec, Adekunle Moshood; Mohammed, Jibril; Markus, Markus (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
In this study, characterization of agricultural waste (oil palm empty fruit bunch, coconut shell and cassava peel) was done before and after carbonization. Briquettes were produced from the carbonized OPEFB and CS blends with CP as binder. Muffle furnace was used for the carbonization of both biomass; CS was carbonized at 7000C at 60 minutes residence time and OPEFB was carbonized at 4000C at 30 minutes residence time. Proximate analysis showed that raw OPEFB and CS had volatile matter of 70.89 and 63.76wt% which indicates easy ignition but high burning rate. They had low fixed carbon of 18.13 and 17.60wt% for OPEFB and CS respectively which accounted for their low calorific value of 19.61 and 20.70 MJ/kg respectively. Ultimate analysis showed insignificant nitrogen and sulfur content from both biomass. The carbonized OPEFB and CS showed improved Calorific value of 28.38 and 27.91 MJ/kg respectively. This was as a result of devolatilization of the biomass with enrichment of carbon from 45.04 to 69.28wt% for OPEFB and 48.02 to 75.50wt% for CS. The briquettes formed had a mean calorific value, compressive strength, burning rate and density of 27.40 MJ/kg, 2.138 N/mm2, 1.110 g/min and 912.26 kg/m3respectively. With these performance indicators, these selected agricultural wastes biomass could be helpful for production of fuel alternatives for domestic heating in developing and underdeveloped countries that produce such waste.